2017
DOI: 10.1016/j.apcata.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the effects of reaction temperature and flow rate on the conversion of ethanol to 1,3-butadiene

Abstract: A full factorial experimental design was performed to investigate the conversion of ethanol to 1,3-butadiene (1,3-BD), through manipulation of the reaction temperature and ethanol weight hourly space velocity. Reactions were carried out in presence of the catalyst K2O:ZrO2:ZnO/MgO-SiO2, prepared by co-precipitation methods. Mathematical models were developed to correlate observed product selectivities, 1,3-BD yields and productivities with the manipulated reaction variables, allowing for quantification of vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 43 publications
3
24
0
Order By: Relevance
“…The catalytic results at different reaction temperatures, space velocities (WHSV), and water contents in the ethanol feed are gathered in Table S1 of temperature and pressure of the tests, and linearly decreases with WHSV as the contact time diminishes. This behaviour has also been reported for other one-step catalysts in the previous literature [9,35,[38][39][40]. [33].…”
Section: Effect Of Temperature and Space Velocitysupporting
confidence: 87%
See 1 more Smart Citation
“…The catalytic results at different reaction temperatures, space velocities (WHSV), and water contents in the ethanol feed are gathered in Table S1 of temperature and pressure of the tests, and linearly decreases with WHSV as the contact time diminishes. This behaviour has also been reported for other one-step catalysts in the previous literature [9,35,[38][39][40]. [33].…”
Section: Effect Of Temperature and Space Velocitysupporting
confidence: 87%
“…On the other hand, at constant WHSV, 1,3-butadiene selectivity presents a maximum with temperature due to the fact that the formation of ethene exponentially rises at higher temperatures. Regarding ethanol conversion, it always rises with contact time and temperature [9,18,[38][39][40][41]. So far, the most complete study on the effect of reaction conditions has been reported by Simoni Da Ros et al [38], who applied statistical experimental design to assess the effect of temperature and space velocity over a K2O-ZrO2-ZnO/MgO-SiO2 catalyst feeding pure ethanol diluted with inert gas.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 In addition, low butadiene productivity could hinder the economic viability of the process, 13 but attaining high butadiene space-time yield by increasing the ethanol flow rate was found to coincide with lower selectivity. 16 Catalyst design can help overcoming these limitations by improving performances in the Lebedev process. However, this requires a better understanding of the structure-activity relationship so that new materials are tailored for optimal catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…The Lebedev-process [3] where the ethanol is converted to BD over mixed oxide catalyst, like MgOÀ SiO 2 or ZnO-Al 2 O 3 , and the process of Ostromislensky [4] where a mixture of ethanol and acetaldehyde is reacted over alumina or clay catalysts. Recently, different oxides, mixed oxides, and zeolite supported catalysts, such as, SiO 2, [5][6][7][8] SiO 2 -ZrO 2, [9] zeolite Beta, [10] and MgOÀ SiO 2 [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] promoted with metals and/or metal oxides, such as oxides of Zn, [8,9,17,24,25,27] Ag, [10,27,28] Cu, [10,27] Au, [11] and Ga, [15,29] and metal combinations, like Zn-Hf, [5] Zn-Ta [7,30] and Zn-Zr [13,23,26] have been reported to be active in the ETB process.…”
Section: Introductionmentioning
confidence: 99%